Magnetically driven active topography for long-term biofilm control - Huan Gu (Nature Portfolio, 2020)
Biofilm formation is a major problem in indwelling medical devices. Here, the authors report on the development of a magnetically responsive micro pillar surface for the controlled prevention and removal of biofilms which also increased sensitivity to antibiotics.